Price Leadership and Welfare Losses in U.S. Manufacturing - Gisser, Micha (American Economic Review, 1986)
A model of price leadership is used to estimate the welfare losses due to monopoly in U.S. manufacturing. Given that the leaders behave independently, an hypothesis confirmed empirically, the deadweight loss is estimated at 0.114 percent of GNP based on a sample of 445 four-digit industries.